Base cation stimulation of mycorrhization and photosynthesis of sugar maple on acid soils are coupled by foliar nutrient dynamics - St Clair, Samuel B (The New phytologist, 2005)
The nutritional benefits that mycorrhizal associations provide to plants may be constrained by acidic soil conditions resulting in decreased photosynthetic function. Sugar maple (Acer saccharum) and red maple (Acer rubrum) seedlings were grown on a native acidic (pH 4.1) soil both unamended and amended with base cations (pH 6.2). In a second study a fungicide treatment was included. Foliar nutrition, mycorrhizal colonization, photosynthesis and their relationships were assessed. On the native soil, red maple maintained higher levels of mycorrhizal colonization and photosynthesis than sugar maple but showed little response to base cation amendments. Mycorrhizal colonization and photosynthesis of sugar maple increased significantly in response to base cation amendments. Correlations were observed among mycorrhizal colonization, foliar nutrition and photosynthesis. The fungicide treatment indicated that 50% of the base cation-induced increase in sugar maple photosynthesis was mycorrhiza related. The results suggest that base cation stimulation of mycorrhization and photosynthesis of sugar maple on acid soils are coupled by foliar nutrient dynamics. Red maple exhibits much less sensitivity to these same edaphic conditions